Effect of COVID-19 for cancer screening and cancer treatment in Japan - Dr Hirokazu Takahashi; Ms. Ryoko Machii (International Journal of Infectious Diseases)
Introduction: The COVID-19 pandemic has had a major impact on cancer screening and medical care in many countries. In Japan, with regard to cancer screening, less urgent medical services have been refrained from due to notifications from the Ministry of Health, Labor and Welfare and related medical societies. As a result, the number of cancer screenings, cancer patients, and less urgent surgery decreased in 2020. Methods: The number of people who received cancer screening and the number of cancer cases in government statistics were monitored from 2019 to 2022, and trends by cancer type were compared. Results: The number of cancer screenings decreased significantly in 2020, after that recovered and decreased by about 20% in the annual comparison. The number of cancer patients decreased significantly in cancer screening-related cancers and areas where the infection spread. Surgery was significantly reduced in cancer screening-related cancers, asymptomatic elective surgery, and areas of widespread infection. Discussion: Although this trend improved in 2021 to 2022, the number of gastric cancer patients continues to decline, suggesting that access to cancer screening and medical care continues to be hindered. Conclusion: It is important to maintain health equity because of the concern that the number of people with advanced cancer will increase and the number of cancer deaths will increase in the future.